ANALISIS HARGA POKOK PRODUKSI USAHA INDUSTRI PERABOT DI KECAMATAN TAMPAN KOTA PEKANBARU TAHUN 2012 - DEVIANA DEVIANA; Rina Selva Johan; Riadi Armas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThis research was conducted at the furniture industry business in the Kecamatan Tampan Kota Pekanbaru that produces regular romawi chair, where the usual romawi chair is a type of chair that is most in demand by consumers. The aim is to analyze the cost of goods sold (HPP) in the furniture industry business in the Kecamatan Tampan Kota Pekanbaru useful as a reference in determining the selling price and to determine the amount of profit earned per unit of effort for the furniture industry product regular romawi chair.Collecting data through interviews and documentation. Data analysis using quantitative descriptive analysis is then performed calculation of the cost of goods sold (HPP) per unit and profit per unit.The results obtained after the calculation of the cost of goods sold per unit and profit per unit, namely: the cost of goods sold per unit of each business furniture industry for product type romawi chair at the highest ordinary effort